An experimental study on mechanical, shrinkage and creep properties of early-age concrete affected by clay content on coarse aggregate. (June 2022) - Zhou, Yuqi; Du, He; Liu, Yuhang; Liu, Jiankun; Liang, Siming
Abstract: The presence of clay particles on coarse aggregate is usually encountered in actual field conditions and may have an adverse influence on concrete properties. However, several aspects concerning the clay content of coarse aggregate (e.g., its influence on the creep and crack risk of early-age concrete) are still unclear. This study investigated the influence of montmorillonite clay content of coarse aggregate on mechanical properties, shrinkage, and creep of early-age concrete by a series of experimental tests. Concretes with coarse aggregate containing 0.0%, 1.5%, and 3.0% montmorillonite clay were prepared for the experimental tests. The results show that the montmorillonite clay attached to coarse aggregate has a significant influence on the mechanical properties, shrinkage, and creep of early-age concrete. As the montmorillonite clay reaches 3.0%, compressive strength, flexural strength, and elastic modulus will decrease by 36.8%, 32.9%, and 38.3%, respectively; while the shrinkage and creep will increase by 31.4% and 45.5%, respectively. The deterioration of the interfacial transition zone due to montmorillonite clay attached to coarse aggregate can account for the decrease in mechanical properties and increase in shrinkage and creep. A greater amount of montmorillonite clay attached to coarse aggregate will lead to a weaker aggregate-paste bond. The findings can contribute to a better assessment of the early-age crack risk of the concrete structures.